FPGA-based adaptive linear-line approximation and implementation for optimum photovoltaic device power control - Mohandas, R; Omkumar, S; Kumar, T Rubesh; D Rukmani Devi (Journal of physics. Conference series, 2021)
Photovoltaic technology is one of the greatest attractions among the various renewable energy sources, coupled with the availability of atmospheric temperature in quantity and without emissions of greenhouse gases due to its poor PV power. Therefore, networking opportunities lie in applying electrical power generation and transmission methods to produce voltage level with favorable rates for effective application. The photovoltaic panel’s suitable methodology is important for analyzing, controlling, and monitoring a PV generator’s design. The photovoltaic system is the basic component of a PV device, so the PV array needs to be run at the highest power point to optimize the system’s energy production. In the system, a solar tracking system is needed to function at the maximum power point. The characteristics of a PV cell’s output power and energy are semi, and therefore its output fluctuates in compliance with the difference in solar irradiation and temperature. An amount of studies has been aimed at designing successful MPPT schemes over the last decade. Research projects are still increasing interesting; however, discovering building FACTS devices and resolving their digital quality issues. Besides, the architecture of MPPTs that could cope with irradiance and temperature is difficult. The establishment of innovative strategies and transmitted source inverter control techniques for a PV device with different pulse widths. To build a filter that remove the solar array PV panel’s using current instantaneous reactive power. The voltage regulation filter based mostly on PV array is then configured with adjusted adaptive threshold control with sequence analysis size. The MATLAB simulator and FPGA and legitimate digital numerical simulations are expected to show strong harmonic adjustment for the existing PV-based SAPF.